Palestinian Administrative Investigation and Judicial Commissions in the Scale of Justice and Fairness / Palestine Al-Bireh Municipality Administrative Investigation Case study - Al-Taweel, Ziyad Said (Journal of Economic, Administrative and Legal Sciences, 2023)
In the study, the researcher first studied and investigated the committees formed by the national authority from its various aspects, in term of the investigation committees that are formed by the executive authority at the theoretical and practical level and the legal basis for them, as well as clarifying the nature of its specialization, then the researcher dealt with conducting the administrative investigation and the extent of the control authority's authority in referral for investigation and the precautionary measures taken against the employee referred to investigation, and the implication thereof.Secondly, the researcher restored to the applied part, which is the negative administrative position of the municipality of the city of Al-Boreh in the state of Palestine, taking in it a summary statement of the decision to dismiss the named Ziyad Al-Tweel by the investigation authority, then a statement of the documents presented by him, which confirms that the dismissal decision was unfair and slandered , and then a statement of the facts that called for appealing this decision.
Keywords: administrative investigation; administrative judiciary; Palestine; Al-Bireh municipality